Challenges of Digitalization In The Economy: The Penetration of Sharia Fintech in Aceh - Rosalina, Dhian; Nurhayati, Nurhayati; Anggraini, Tuti (Mahesa Research Center, 2025)
Most coastal communities engage in fishing and simultaneously operate as MSMEs (Micro, Small, and Medium Enterprises) that drive the coastal economy. Unequal access to financial services from banks and other financial institutions has created obstacles for MSMEs in accessing financial services. Financial technology (fintech) has become a viable economic solution supporting MSME development by providing quick, affordable, and accessible services.In Aceh Province, where Sharia law is implemented in economic activities, one of the government policies through Bank Indonesia in 2023—